Gender, tenure security, and landscape governance: Synthesis of studies of PIM’s Governance of Natural Resources flagship program 2013-2020 - Kristjanson, Patricia (International Food Policy Research Institute, 2021)
Gender relations influence people’s access to, use and management of land and other natural resources. They also influence, and are influenced by, ownership, tenure and user rights to land and forests. Policies and interventions aimed at improving the governance of natural resources and landscapes need to benefit women as well as men. A failure to address differing needs, roles and responsibilities of women and men, and underlying gender relations and how they are changing, reduces their effectiveness and will risk perpetuating gender inequality. This study synthesizes the contribution of the CGIAR Program on Policy, Institutions and Markets (PIM) flagship on Governance of Natural Resources to knowledge regarding gender and its influence on tenure security and landscape governance. It discusses the scientific contributions to the broader wealth of related literature by analyzing and summarizing key lessons about gender from these studies, where possible, with respect to outcomes and impacts in natural resource management, food security, and poverty alleviation. This information will help researchers better communicate the salience of the Flagship’s research for current and prospective donors and other partners, in order to influence strategies and interventions aimed at addressing challenges related to these three arenas.